Clinical Study on the Relationship between the SNP rs8192675 (C/C) Site of SLC2A2 Gene and the Hypoglycemic Effect of Metformin in Type 2 Diabetes. (31st January 2022) - Ye, Weiwei; Wang, Yi; Chen, Feng; Zhao, Qian; Meng, Xiangying; Chen, Jianyang; Liu, Cong; Zhou, Yong
Abstract : This study investigates the correlation between the gene polymorphism of rs8192675 (C/C) locus of SLC2A2 in patients with type 2 diabetes (T2DM) and the efficacy of metformin. For this purpose, we have selected 110 T2DM patients (T2DM group) and 110 healthy people (control group) who were treated in our hospital from January 2019 to January 2020 as the research subjects. PCR-restriction fragment length polymorphism (PCR-RFLP) method detects the distribution frequency of gene polymorphism. The patients in the T2DM group were treated with metformin and followed up for 90 days to analyze the relationship between the efficacy of metformin and the SLC2A2 gene polymorphism. The genotypes of SLC2A2 rs8192675 in the control group and in the T2DM group conformed to the Hardy–Weinberg equilibrium law. Compared with the control group, the CT type and the CC type at rs8192675 in the T2DM group were significantly higher (P < 0.05 ). For rs8192675, there was no significant difference in TT, CT, CC FPG, 2hPBG, and HbA1c levels before treatment (P > 0.05 ); after metformin treatment, the reduction in FPG, 2hPBG, and HbA1c in CC patients was lower than that of TT and CT patients (P < 0.05 ). SLC2A2 gene polymorphism site rs8192675 CC type T2DM patients are sensitive to metformin and have a better hypoglycemic effect.